2022
DOI: 10.2196/39519
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use and Well-being With Bipolar Disorder During the COVID-19 Pandemic: Path Analysis

Abstract: Background Reliable and consistent social support is associated with the mental health and well-being of persons with severe mental illness, including bipolar disorder (BD). Yet the COVID-19 pandemic and associated social distancing measures (eg, shelter in place) reduced access to regular social contacts, while social media use (SMU) increased concomitantly. Little is currently known about associations between the well-being of adults with BD and different types of SMU (eg, passive and active). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…On Facebook, it has been found that more than half their sample Facebook users chose to represent depression symptom displays on Facebook as adolescents than young adults [25]. But the other research indicates that passive Facebook users with Bipolar Disease during the COVID-19 pandemic show depressive symptoms were negatively associated with both social support and life satisfaction and positively associated with loneliness [26]. As additional information, a new deep learning model with natural language processing methods has been made to identify the users with potential mental illness based on their posts on Reddit.…”
Section: Discussionmentioning
confidence: 99%
“…On Facebook, it has been found that more than half their sample Facebook users chose to represent depression symptom displays on Facebook as adolescents than young adults [25]. But the other research indicates that passive Facebook users with Bipolar Disease during the COVID-19 pandemic show depressive symptoms were negatively associated with both social support and life satisfaction and positively associated with loneliness [26]. As additional information, a new deep learning model with natural language processing methods has been made to identify the users with potential mental illness based on their posts on Reddit.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from qualitative studies suggest that people with severe mental health conditions, such as BD, actively seek out ways to communicate with their peers online and that peer support naturally happens among individuals who share their experiences online. Research also points to the potential for social media to confer peer support to those with BD, either as a supplement or alternative to in-person support [ 11 ]. Having more healthcare professionals get involved in using social media platforms to share information about BD will help users find more relevant and reliable information about the disorder and reduce misconceptions on these platforms [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research also points to the potential for social media to confer peer support to those with BD, either as a supplement or alternative to in-person support [11]. Having more healthcare professionals get involved in using social media platforms to share information about BD will help users find more relevant and reliable information about the disorder and reduce misconceptions on these platforms [12].…”
Section: Discussionmentioning
confidence: 99%
“…For the BADAS study, an international sample of young and older adults with BD was recruited using microtargeted Facebook advertising [17][18][19]. Recruitment notices were sent only to those with "BD interests" (a euphemism used by Facebook to avoid diagnostic labels).…”
Section: Recruitment and Data Collectionmentioning
confidence: 99%